2017
DOI: 10.1002/2016ja023488
|View full text |Cite
|
Sign up to set email alerts
|

MAVEN observations of tail current sheet flapping at Mars

Abstract: The Martian magnetotail is a complex regime through which atmospheric particles are lost to space. Our current understanding of Mars' tail continues to develop with the comprehensive particle and field data collected by Mars Atmosphere and Volatile EvolutioN (MAVEN). In this work, we identify periods when MAVEN encounters multiple current sheet crossings through a single tail traversal in order to understand tail dynamics. We apply an analysis technique that has been developed and validated by using multipoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 54 publications
(105 reference statements)
2
46
1
Order By: Relevance
“…These two arguments make unlikely to explain these measurements in terms of an IMF rotation, and, since the model considers effects derived from CFs, we conclude that the observed polarity change in the tail lobe is likely due to flapping (steady or kink) of the neutral current sheet. Similar signatures have been recently reported and studied based on MAVEN data (DiBraccio et al, , ). Indeed, multiple current sheet crossings are often observed on any given orbit as MAVEN crosses the Martian magnetotail, under stable IMF conditions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These two arguments make unlikely to explain these measurements in terms of an IMF rotation, and, since the model considers effects derived from CFs, we conclude that the observed polarity change in the tail lobe is likely due to flapping (steady or kink) of the neutral current sheet. Similar signatures have been recently reported and studied based on MAVEN data (DiBraccio et al, , ). Indeed, multiple current sheet crossings are often observed on any given orbit as MAVEN crosses the Martian magnetotail, under stable IMF conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Draping of the IMF is well reproduced in both direction and magnitude during the majority of the studied event. Numerical simulations do not reproduce the B x component between 08:00 and 08:14:30 UT where a change of sign is observed and difficult to interpret with a stationary picture of magnetic field draping, suggesting magnetotail flapping in the absence of IMF variabilities (DiBraccio et al, , ). The main difference at high altitudes concerns the predicted BS location, particularly during the flank BS crossing.…”
Section: Numerical Simulation Results and Comparison With Maven Datamentioning
confidence: 99%
“…Using the four‐point analysis of the Cluster (Escoubet et al, ), many studies demonstrated that the flapping CS can propagate as kink‐like waves from the midnight region toward both magnetotail flanks, with a velocity of several tens of km/s (Petrukovich et al, ; Rong et al, ; Runov et al, ; Sergeev et al, , ; Shen et al, ; Sun et al, ; Zhang et al, , ). CS flapping motions are observed not only in the Earth's magnetotail but also in the magnetotails of other planets, such as Mercury (Poh et al, ), Venus (Rong, Barabash, Stenberg, Futaana, Zhang, Wan, Wei, Wang, Chai, et al, ), Mars (DiBraccio et al, ), Saturn, and Jupiter (Volwerk et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies based on the four‐point analysis of Cluster (Escoubet et al, ) demonstrate that the flapping motions can propagate as kink‐like waves from midnight toward both magnetotail flanks with the velocity of several tens of km/s (Petrukovich et al, , ; Rong et al, ; Runov et al, ; Sergeev et al, , ; Shen et al, ; Zhang et al, , ). In addition to Earth's magnetotail, the flapping motions are also commonly observed in planetary magnetotails, such as Mercury (Poh et al, ), Venus (Rong, Barabash, Stenberg, Futaana, Zhang, Wan, Wei, Wang, Chai, et al, ), Mars (DiBraccio et al, ), Saturn, and Jupiter (Volwerk et al, ).…”
Section: Introductionmentioning
confidence: 99%